ChemInform Abstract: Practical Iron‐ and Cobalt‐Catalyzed Cross‐Coupling Reactions Between N‐Heterocyclic Halides and Aryl or Heteroaryl Magnesium Reagents. Issue 40 (October 2015) - Kuzmina, Olesya M.; Steib, Andreas K.; Fernandez, Sarah; Boudot, Willy; Markiewicz, John T.; Knochel, Paul
Abstract The title reaction is applied to pyridyl, pyrimidinyl, and 1, 3, 5‐triazoyl halides and a variety of arylmagnesium halides.